Art and Culture in Character Education - Ridwan, Ridwan; Narawaty, Taty; Karwati, Uus; Sukmayadi, Yudi; Nikawanti, Gia (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Art is closely related to education have the functionality to build a foundation to communicate, build creativity, realize human civilization, develop psychological abilities, build discipline, preparing for adulthood, fostering artistic assessment, and can make the learner 's become more enjoyable. In an effort to develop cultural education and national character, character education based on local wisdom can be used as a tool that can be used in shaping a generation of quality people. Moral values can be applied through art so they can build character which is the main foundation of the formation of a civilized and prosperous society. One of the arts that instills character values is Songah in the Citengah Village of Sumedang Regency. The purpose of this study is to provide an overview of the relationship between Songah and character education based on local wisdom. With a descriptive qualitative approach revealed the relationship between songah and character education based on local wisdom. The results of this study indicate that Songah has a great influence on the development of cultural education and national character, especially in the communities around the arts through high values be contained in Songah